#TITLE_ALTERNATIVE# - P. H. S (NIM : 12507010), DONO
New class material Al-Foam has a low density with high stiffness. The combination of the unique properties makes Al-Foam application potential for lightweight structures, energy management, thermal management and heat transfer, sound absorpsion, and the vibration suppression. As one of the metal foam, Al-Foam is currently still under development and research, and still unfamiliar among most engineer. Closed cell ALPORAS Al-Foam were produced by Sinko Wire Co. Japan with batch casting method, using Al-Ca as base composition and TiH2 as foaming agent. Characterization begins by measuring the density and relative density. Surface contour was taken by scanning the surface and image analysis is prepared to use the Optimas 6.1 to calculate the average diameter of the cells and cells surface area. Optical microscope used to view surface and cell wall morphology. Observation of microstructure and composition analysis using SEM and EDS. Hardness tests using a Vickers Hardness. Loading-unloading on compression test deformation rate 0.08 mm/s was performed at strain 2%, 5%, 10%, and %35 and stops at 75% strain to see the changes in E. Then do measure ζys, ζpl, εD and from the first compression test the energy absorbed was calculated. The results of displacement measurements at 0.1 strain or 5 mm by the Material Testing Machines compared to a dial gage measuring 10 μm, by changing a video with 28 FPS to 3524 images for image analysis. Recording compression test was done to see the direction of slip and deformation bands on cells. Then analyse the relation between relative density and to the properties. The measurement results and analysis indicate that Alporas has a density 0.41 gr/cm3, relative density 0.15 showing that Al-Foam is very potential for ultralight structure application. Average cells diameter 2.43 mm, Hardness 25 HVN, E 0.16 GPa, ζys 1.59 MPa, densification strain 0.74. E increased 110% by unloading at strain 35%. Energy absorbed 19.95 KJ per cm3. Relative strength of Al-Foam is a function of it‟s relative density. Displacement measurement using dial gage give higher E up to 78.88 %, and see deformation band with slip band 45o from video analysis.